2018
DOI: 10.1016/j.ajhg.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Missense Variants in TRAF7 Cause Developmental Delay, Congenital Anomalies, and Dysmorphic Features

Abstract: TRAF7 is a multi-functional protein involved in diverse signaling pathways and cellular processes. The phenotypic consequence of germline TRAF7 variants remains unclear. Here we report missense variants in TRAF7 in seven unrelated individuals referred for clinical exome sequencing. The seven individuals share substantial phenotypic overlap, with developmental delay, congenital heart defects, limb and digital anomalies, and dysmorphic features emerging as key unifying features. The identified variants are de no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 37 publications
(47 reference statements)
5
68
1
Order By: Relevance
“…In addition, PALM2-AKAP2 was a potential locus associated with height according to the previous GWAS for the Korean population (Kim et al, 2010). Both biallelic deleterious mutations in NANS and de novo missense variants in TRAF7 have been reported to be associated with developmental delay or severe skeletal dysplasia (van Karnebeek et al, 2016;Tokita et al, 2018). PACSIN1 was also detected as a causal gene for body weight in Meishan pigs (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, PALM2-AKAP2 was a potential locus associated with height according to the previous GWAS for the Korean population (Kim et al, 2010). Both biallelic deleterious mutations in NANS and de novo missense variants in TRAF7 have been reported to be associated with developmental delay or severe skeletal dysplasia (van Karnebeek et al, 2016;Tokita et al, 2018). PACSIN1 was also detected as a causal gene for body weight in Meishan pigs (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…We identified 4 unrelated individuals in a total of approximately 2,450 individuals in an undiagnosed exome cohort in our three institutions. The likelihood of de novo variants in the same residue, c.1732C>T (p.Arg578Cys) or c.3436C>T (p.Arg1146Cys), in MAPK8IP3 in 2 unrelated individuals was calculated to be 2.56 × 10 –9 , using the Poisson model as previously described . This finding remained significant when we corrected for the 18,892 genes targeted in the Consensus Coding Sequence (CCDS release 20; p = 4.83 × 10 –5 ).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly however, Tokita et al recently reported that de novo missense mutations in TRAF7 cause developmental abnormalities and other clinical symptoms in seven unrelated patients, including developmental delay (5/5), congenital heart defects (6/7), limb and digital anomalies (7/7), and dysmorphic facial features (7/7) ( 300 ). TRAF7 mutations identified in this study include a recurrent R655Q mutation found in four patients, and another 3 single mutations each identified in one patient, including K346E, R371G, and T601A ( 300 ). Interestingly, R371 recurrent mutations are also detected in human cancers (Figure 3 ).…”
Section: Traf7mentioning
confidence: 99%
“…Both T601 and R665 are located in the C-terminal WD40 repeats of TRAF7, which contain most mutation hotspots of TRAF7 detected in human cancers (Figure 3 ) and are known to mediate the interaction of TRAF7 with MEKK3 or c-Myb ( 302 , 305 ). Tokita et al further revealed that transfection of the R665Q, T601A, or R371G mutants of TRAF7 into HEK293T cells results in significantly reduced levels of ERK1/2 phosphorylation, both basal and in response to TNFα signaling ( 300 ). Consistent with this biochemical evidence, conditional ERK2 −/− mice show a phenotype mirroring that observed in the seven patients with TRAF7 mutations, including craniofacial abnormalities, cardiovascular malformations and limb defects ( 306 ).…”
Section: Traf7mentioning
confidence: 99%